Peran Theory of Planned Behavior dan Environmental Concern terhadap Green Investment Intention - Candy, Candy; Kelvin, Kelvin; Hesniati, Hesniati (Jurnal Ilmu Manajemen, 2024)
The aim of this research is to examine the green investment intentions of Indonesian investors. The Indonesian government is initiating sustainable development with the new capital city, which is envisioned as a green city. Indonesia faces significant environmental challenges, including air pollution, which ranks the country 26th out of 131 countries with poor air quality, according to the 2022 IQAir report. In response, the government has issued green sukuk to support green projects further. Previous research in many developing countries has utilized the theory of planned behavior as a framework. This study collected primary data by distributing questionnaires to 210 investors in Batam. The data was analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate that green perceived behavioral control and environmental concern have a significant positive effect on green investment intentions. However, green attitude and green subjective norms do not directly influence green investment intentions. The findings highlight that green perceived behavioral control and environmental concern are critical factors in shaping investment intentions, suggesting that investors' actions are driven by internal motivations and environmental concerns